Perconcentration of Trace Cr(III) using Octadecyl Silica Membrane Modified N,N-Disalicylideneethylenediamine - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2011)
A novel and selective method for the fast determination of trace amounts of Cr(III) ions in water samples has been developed. The procedure is based on the selective formation of chromium N,N-disalicylideneethylenediamine (NNDED) complexes at optimum pH by elution with organic eluents and determination by atomic absorption spectrometry.The method is based on complex formation on the surface of the ENVI-18 DISKTM discs followed by stripping of the retained species by minimum amounts of appropriate organic solvents. The elution is efficient and quantitative. The effect of potential interfering ions, pH, ligand amount, stripping solvent and sample flow rate were also investigated. Under the optimal experimental conditions, the break-through volume was found to about 1000 mL providing a preconcentration factor of 500. The maximum capacity of the discs was found to be 389 ± 4 μg for Cr3+. The limit of detection of the proposed method is 5 ng per 1000 mL. The method was applied to the extraction and recovery of chromium in different water samples.